Employer Branding and E-recruitment Against Interest in Applying for Generation Z Jobs - Geofanny, Ravika; Faraz, Faraz (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
This study aims to determine how employer branding and e-recruitment influence the intention to apply for a job of Z Generation. This research is a quantitative study with 203 Z Generation As the Samples. This study uses three kinds of scales, including employer branding scale, Acceptance model of e-recruitment scale to measure how Z Generation’s Intention toward using e-recruitment, and an Intention towards company scale to measure how much Intention that Z Generation had to Apply for a job. The data analysis technique used in this research is multiple linear. The results of this study indicate that there is an influence of employer branding to the interest in applying for jobs of Z generation (t = 0.000 < 0.05). There is an influence from e-recruitment to the interest in applying for jobs of Z generation (t = 0.007 < 0.05). There is an effect of employer branding and e-recruitment on the interest in applying for generation Z jobs F count 40,520 with a significance value of 0.000 <0.05 (α = 5%). Based on the results, companies can use employer branding and e-recruitment as strategies to attract the interest of Z Generation in applying for jobs. This is also a solution to overcome the tendency of many generations Z who refuse to work in a company.Penelitian ini bertujuan untuk mengetahui bagaimana pengaruh employer branding dan e-rekrutmen terhadap minat melamar pekerjaan Generasi Z. Penelitian ini merupakan penelitian kuantitatif dengan Sampel 203 orang generasi Z. Penelitian ini menggunakan tiga jenis skala, yaitu skala employer branding, Skala model penerimaan e-recruitment untuk mengukur bagaimana minat Generasi Z dalam menggunakan e-recruitment, dan skala minat terhadap perusahaan untuk mengukur seberapa besar minat Generasi Z untuk melamar pekerjaan. Teknik analisis data yang digunakan dalam penelitian ini adalah regresi linier berganda. Hasil penelitian ini menunjukkan bahwa terdapat pengaruh employer branding terhadap minat melamar pekerjaan generasi Z (t=0,000 < 0,05). Terdapat pengaruh e-recruitment terhadap minat melamar pekerjaan generasi Z (t=0.007 < 0,05). Terdapat pengaruh employer branding dan e-rekrutmen terhadap minat melamar pekerjaan generasi Z dengan F hitung sebesar 40.520 dengan nilai signifikansi 0,000 < 0,05 (α=5%). Berdasarkan hal tersebut, perusahaan dapat menggunakan employer branding dan e-recruitment sebagai strategi menarik minat melamar pekerjaan Generasi Z. Hal ini sekaligus menjadi solusi mengatasi kecenderungan banyaknya Generasi Z yang menolak bekerja di sebuah perusahaan.